2011
DOI: 10.1007/s12013-011-9158-8
|View full text |Cite
|
Sign up to set email alerts
|

Fluid Dynamics of Heart Development

Abstract: The morphology, muscle mechanics, fluid dynamics, conduction properties, and molecular biology of the developing embryonic heart have received much attention in recent years due to the importance of both fluid and elastic forces in shaping the heart as well as the striking relationship between the heart's evolution and development. Although few studies have directly addressed the connection between fluid dynamics and heart development, a number of studies suggest that fluids may play a key role in morphogenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
71
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 62 publications
(72 citation statements)
references
References 105 publications
(122 reference statements)
1
71
0
Order By: Relevance
“…Extensive study of intracardiac fluid forces during cardiovascular development has demonstrated important roles in valvulogenesis and trabeculation [1,2,37,38]. Our results suggest that cardiogenesis is also regulated by extracardiac flow forces generated in the pericardial cavity.…”
Section: Discussionmentioning
confidence: 56%
“…Extensive study of intracardiac fluid forces during cardiovascular development has demonstrated important roles in valvulogenesis and trabeculation [1,2,37,38]. Our results suggest that cardiogenesis is also regulated by extracardiac flow forces generated in the pericardial cavity.…”
Section: Discussionmentioning
confidence: 56%
“…In the heart, the highest level of X-gal staining at E11.5 was observed in the endothelium lining ventricular outflow tract and atrioventricular canal (Fig. 2C), areas predicted to experience strong fluid shear forces generated by blood flow (30,31).…”
Section: Piezo1mentioning
confidence: 99%
“…However, the influence of mechanical forces and its synergy with tissue architecture in influencing cardiac valve EMT is unknown. During embryonic development, valve morphogenesis has been correlated with an increase in fluid shear stresses, mechanical strains, and altered geometry of the developing heart (19)(20)(21)(22). These observations potentially suggests interaction between mechanical forces and the factors that regulate EMT.…”
mentioning
confidence: 99%